V=2.28943
I am not sure though
Answer:
![3(x - 4) = - 3 \\ 3x + 12 = - 3 \\ 3x = - 15 \\ x = - 5](https://tex.z-dn.net/?f=3%28x%20-%204%29%20%3D%20%20-%203%20%5C%5C%203x%20%2B%2012%20%3D%20%20-%203%20%5C%5C%203x%20%3D%20%20-%2015%20%5C%5C%20x%20%3D%20%20-%205)
Firstly, multiply the number and variable in the perenthesis. Then move the variable on it's own side of the equation. The simplify.
Answer:11
Step-by-step explanation: think about 5+6 then when you add 11 to the -5 you get 6.
Answer:
x=8
Step-by-step explanation:
Triangle DCE is similar to EGF
CE/EF=DE/EG
Substitute
(8x-1)/21=(6x+3)/17
Cross multiply
(8x−1)*(17)=(6x+3)*(21)
136x−17=126x+63
Subtract 126x from both sides
10x−17=63
Add 17 to both sides.
10x−17+17=63+17
10x=80
Divide both sides by 10.
x=8